2022
DOI: 10.3390/molecules27227702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structured Phenolic Lipids with EPA/DHA and Gallic Acid against Metabolic-Associated Fatty Liver Disease (MAFLD) in Mice

Abstract: Obesity is the leading risk factor for developing metabolic (dysfunction)-associated fatty liver disease (MAFLD). The food industry has an essential role in searching for new strategies to improve primary food sources to revert some of the metabolic alterations induced by obesity. There is consistent evidence that long-chain polyunsaturated fatty acids (n-3 LCPUFA) belonging to the n-3 series, i.e., eicosapentaenoic (20:5n-3, EPA) and docosahexaenoic (22:6n-3, DHA) acids, could revert some alterations associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
1
0
0
Order By: Relevance
“…As shown in Figure 1, S LBL and MLBL interventions did not significantly improve high-fat diet induced obesity, which the similar phenomena were reported by Dovale-Rosabal et al [17] These phenomena might be related to the additional energy provided by lauric acid produced by S LBL and MLBL after digestion. Xia et al found that TC and LDLC levels in obese rats were paradoxically higher after triglyceride laurate treatment.…”
Section: Discussionsupporting
confidence: 85%
“…As shown in Figure 1, S LBL and MLBL interventions did not significantly improve high-fat diet induced obesity, which the similar phenomena were reported by Dovale-Rosabal et al [17] These phenomena might be related to the additional energy provided by lauric acid produced by S LBL and MLBL after digestion. Xia et al found that TC and LDLC levels in obese rats were paradoxically higher after triglyceride laurate treatment.…”
Section: Discussionsupporting
confidence: 85%